Continuity and Change in the Family System Across the Transition from Adolescence to Emerging Adulthood. Issue 4 (19th May 2017) - Lindell, Anna K.; Campione-Barr, Nicole
ABSTRACT: As adolescents move into emerging adulthood, their social networks shift toward a focus on peers and romantic partners, yet parents and siblings remain important sources of support. The present review takes a family systems approach to integrate the growing body of literature examining longitudinal continuity and change in both positive (e.g., intimacy, support) and negative (e.g., conflict, rivalry) qualities of parent–child and sibling relationships as adolescents transition to emerging adulthood. In general, contact with family members decreases, yet the quality of family relationships appears to improve or, at the very least, stabilize across this transition. These pathways are interpreted within the lens of several prominent theories, and a discussion of the limitations of the current literature and ideas for future research are presented.